(untitled) (The Journal of Psychology and Sociology, 2023)
In recent years, the process of training and retraining of aviation personnel has become increasingly important in the aviation sphere, as one of the key factors influencing the reduction in the number of avia-tion accidents and incidents. The article describes one of the methods for applying new standards and requirements of the aviation sphere to the concept of competence of air traffic controllers (ATC) instructors, describes previous studies on the psychological and pedagogical aspects of the ATC instructor’s activity, considers the concept of "pedagogical communication", its connection with the competence of an instruc-tor; the features of pedagogical communication between the ATC instructor and the trainee in the learning process are described, various styles of pedagogical communication according to S.A. Shein are analyzed. This paper shows results of the study of air traffic controllers – instructors’s pedagogical communication styles, according to Shane; there are given recommendations for choosing the most optimal style in the in-teraction between the air traffic controller-instructor and the trainee. The purpose of the study was to study the peculiarities of the pedagogical style of communication between an air traffic controller-instructor and trainees. The working documents on the training of aviation personnel, the requirements and recommen-dations of international aviation organizations were studied, and they were compared the competencies of instructors with the styles of their pedagogical communication with trainees. The scientific significance of the work lies in the analysis of the psychological and pedagogical component of the interaction between the instructor and the trainee, the study of a separate component of the instructor’s work in the light of the new requirements of the aviation industry. The practical significance lies in the information obtained about the styles of pedagogical communication of current instructors, which can be used in the selection of candidates for the position of instructor and in advanced training courses and, thereby, increase the ef-fectiveness of training. The methodology of the study consisted in the analysis of aviation guidelines and the application of a questionnaire according to the method of S.A. Shein. In the course of experimental work, the styles of pedagogical communication of instructors were determined. The results of the study indicate the need to pay enough attention to the modern understanding of the competence of instructors in advanced training courses, to find teaching methods for instructors that allow them to develop their own optimal style of pedagogical communication, introduce the skills of cooperation, mentoring, ethics and honesty and prevent the emergence and development of opposite qualities. Key words: competence of ATC instructor, style of psychological and pedagogical communication, human factor, instructor skills.